Modification of copper-based zeolite 13X for methanol and aromatic compound synthesis in microwave plasma–assisted carbon dioxide conversion - Pimchanok Tapangpan; Dheerawan Boonyawan; Saranphong Yimklan; Yothin Chimupala; Arlee Tamman; Supaphorn Thammakan; Takron Opassuwan; Mudtorlep Nisoa; Choncharoen Sawangrat (Case Studies in Chemical and Environmental Engineering)
The direct conversion of carbon dioxide (CO2) into valuable products holds significant potential for advancing a sustainable circular carbon economy. Herein, bifunctional catalysts—copper (Cu)-based zeolite 13X—were modified to enhance methanol and aromatic synthesis in microwave plasma–assisted CO2 conversion. The Cu oxidation state and surface basicity of the modified catalysts were adjusted through thiourea reduction and confirmed via X-ray photoelectron spectroscopy, H2 temperature-programmed reduction, and CO2 temperature-programmed desorption techniques. The results of the investigated catalytic activity of modified CuI/II-based zeolite 13X, pristine zeolite 13X, and plasma alone in microwave plasma–catalytic CO2 conversion revealed that the microwave plasma–assisted catalyst could effectively and directly convert CO2 into valuable products—methanol, benzene, and toluene—without intermediate purification. This catalyst system considerably improved CO2 conversion rate (>50 %) compared with only 18.5 % conversion with the plasma alone catalyst, while the %Selectivity toward methanol and aromatics was >45 %. Additionally, the effects of CuI/CuII ratios and basicity concentrations on methanol and aromatic %Selectivity were investigated. The synergy between the CuI species and surface basicity played a crucial role in promoting toluene and methanol production with low benzene production. The comparable catalytic activities of 0.5 wt% Cu doping with thiourea reduction and 6 wt% Cu doping without thiourea reduction highlighted the efficiency of the thiourea reduction process in economically producing catalysts with fewer metal precursors. Finally, the potential pathways for methanol and aromatic formation were proposed, and the feasibility of industrial scale up was discussed.